2015
DOI: 10.1590/0102-311x00097814
|View full text |Cite
|
Sign up to set email alerts
|

Pontos de venda de alimentos e associação com sobrepeso/obesidade em escolares de Florianópolis, Santa Catarina, Brasil

Abstract: O estudo descreve os pontos de venda de alimentos e sua associação com sobrepeso/obesidade em escolares de Florianópolis, Santa Catarina, Brasil. Desenho transversal com amostra probabilística de 2.506 escolares de escolas públicas (n = 19) e privadas (n = 11). O sobrepeso/obesidade foi classificado pela referência da Organização Mundial da Saúde de 2007. Foram realizadas análises brutas e ajustadas por meio de regressão de Poisson. A prevalência de sobrepeso/obesidade foi de 34,2%. Na rede pública, foram veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 34 publications
0
20
0
7
Order By: Relevance
“…This study is part of a wider research project funded by the Conselho Nacional de Desenvolvimento Científico e Tecnológico analysing the tendency and prevalence of obesity and associated factors among school children (7 to 14 year olds) in Florianópolis. More detailed information about the project is described elsewhere [14]. In this study, a cross-sectional analysis with a probabilistic school-based sample of 11-14-year-old adolescents from public and private schools in Florianópolis was performed.…”
Section: E T H O D Smentioning
confidence: 99%
“…This study is part of a wider research project funded by the Conselho Nacional de Desenvolvimento Científico e Tecnológico analysing the tendency and prevalence of obesity and associated factors among school children (7 to 14 year olds) in Florianópolis. More detailed information about the project is described elsewhere [14]. In this study, a cross-sectional analysis with a probabilistic school-based sample of 11-14-year-old adolescents from public and private schools in Florianópolis was performed.…”
Section: E T H O D Smentioning
confidence: 99%
“…1 Similar trends were observed in Florianópolis, capital of the Brazilian state of Santa Catarina, during the period from 2002 to 2007, among 7 to 10-year-old children, 2 and from 2007 to 2012, among 7 to 14-year-old children and adolescents. 3 In addition, in 2007 and 2008, the prevalence of abdominal obesity among 6 to 10-year-old schoolchildren in the state of Santa Catarina was observed to be 4.9%. 4 Studies have shown that the availability of places for physical activity and active leisure (PAAL) close to home makes it more likely that these facilities will be used more often, because of ease of access.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a study conducted in Florianópolis with families of students aged 7 to 14 years found that 96.4% of the families purchased food in supermarkets 4 . Ease of payment is a possible justification for nearly everyone to shop at supermarkets, since supermarkets accept credit cards and food stamps.…”
Section: Discussionmentioning
confidence: 99%
“…Ease of payment is a possible justification for nearly everyone to shop at supermarkets, since supermarkets accept credit cards and food stamps. Furthermore, because supermarkets offer delivery services 4 , they are more likely to attract families who do not have automobiles.…”
Section: Discussionmentioning
confidence: 99%